Optimizing AltCoin (ETH) Price Synchronization During the Bitcoin Dominance Era: A Comprehensive Phase Analysis with Vector Error Correction Model - Suryawijaya, Tito; Laurent, Fisichella Andrew; Berger, Margot (Economics, Business, Accounting & Society Review, 2023)
The main objective of this research is to optimize the understanding of AltCoin price synchronization, with a focus on Ethereum, during different periods of Bitcoin dominance. This research uses secondary data through 162 observations for each cryptocurrency collected (BTC and ETH). The Vector Autoregressive (VAR)/Vector Error Correction Model (VECM) method is used as the analytical technique. The findings of this study have the potential to provide a strong foundation for the development of investment strategies in the cryptocurrency market. This study has identified different impact patterns on AltCoin prices during the High, Middle and Low Dominance Phases. The research findings reflect different impact patterns depending on the phase of Bitcoin dominance, indicating the complexity of market dynamics related to certain factors.